Association of lifetime e-cigarette and/or tobacco use and last year cannabis use among university students: A cross-sectional secondary analysis of a national survey - Lucero Sangster-Carrasco; Dora Blitchtein-Winicki (Public Library of Science (PLoS), 2022)
Background The accelerated increase in the use of e-cigarette by university students in recent years has incremented nicotine use in addition to tobacco, but it is not known whether the use of cannabis is related to these alternatives. This study analyzes the association between the use of electronic cigarettes and/or tobacco and the use of cannabis in the last 12 months. An analytical cross-sectional study conducted based on the III Andean epidemiological study on drug consumption among university students in 2016. A multivariate analysis performed using a generalized linear family model and the log Poisson link option. The results were shown as Prevalence Ratios (PR) in raw (PRc) and adjusted (PRa) models, and the analysis also employed 95% confidence intervals (95% CI) for the percentages. Setting Ten Peruvian universities. Participants University students' lifetime. Exposure Participants' e-cigarette and/or tobacco consumption, based on questions about consumption of tobacco and e-cigarettes. Participants were categorized into those consuming: only e-cigarettes, only tobacco, both, or neither. Outcome The use of cannabis by participants in the last 12 months. Among the university students who met the inclusion criteria (n = 3981), the prevalence of using both e-cigarettes and tobacco (dual) throughout life was 11.6% (95% CI: 10.1 to 13.3), and only e-cigarettes was 1.2% (95% CI: 0.7 to 1.8). The use of cannabis in the last 12 months was 5.2% (95% CI: 4.1 to 6.5). Results of this study found a sequential probability gradient of cannabis use, where those with dual use had 58.5 times more probability of having used cannabis in the last 12 months (PRa 58.5, 95% CI: 20.9 to 163.7, p <0.001) compared to those who used none; whereas those who used only tobacco were 33.3 times more likely to have used cannabis in the last 12 months (PRa 33.3, 95% CI: 11.9 to 93.2, p <0.001), those who reported using only e-cigarette had 9.8 times more probability of having used cannabis in the last 12 months (PRa 9.8, 95% CI: 1.6 to 60.4, p = 0.014). We found an increase in the probability of having used cannabis in the last 12 months among university students who reported tobacco and/or e-cigarettes use. A sequential probability gradient was found and it showed that, in comparison to students who informed being nonusers of tobacco and/or e-cigarette, university students who were lifetime dual users were most likely to having used cannabis in the last 12 months, followed by those reporting an exclusive lifetime use of tobacco, as well as those students who reported an exclusive lifetime use of e-cigarettes. It is necessary to raise awareness of the association of tobacco and e-cigarette use with an increased possibility of using cannabis. Studies are needed in different cultural contexts to investigate the progression of electronic cigarette and/or tobacco use, as well as their dosage, intensity of use, concurrent use, and neurological and behavioral mechanisms that are related to the use of cannabis and other illegal drugs that may increase dependence and mental health problems.